Plesionika alcocki - Chakraborty, Rekha Devi (Zenodo, 2021)
4.1 Plesionika alcocki (Anderson, 1896) – Fig 1 Pandalus alcocki — Anderson, 1896:92 [type-locality: Laccadive Sea off Malabar Coast of India; 9°34'57"N 75°36'30"E; 743 meters]. Pandalus (Plesionika) alcocki — Alcock and McArdle, 1901, pi. 52: figs. 2, 4. Plesionika alcocki : De Man, 1920: 105; Balss, 1925: 278, fig. 48; Mohamed and Suseelan, 1973; Chace, 1985: 55; Hayashi, 1986: 127, 270, fig. 81; Kensley, Tranter & Griffin, 1987: 313; Dave, 2002: 347; Fransen, 2006: 62-65, fig.17. Material examined: India, Tamil Nadu, Tuticorin fishing port, fishing off Bay of Bengal, 8°47′40"N, 78°09'37"E, 200- 300 m, Jan 2015, 3 males CL 22-25 mm, (CMFRI). 4.2 Plesionika narval (Fabricius, 1787) – Fig 2 (a-k) Astacus narval Fabricius, 1787: 331 (type locality: probably Nice, Mediterranean). Description: Rostrum armed dorsally with 4-6 teeth, ventrally armed with 8-23 teeth becoming obscure anteriorly; orbital margin rather regularly concave; abdomen without posteromesial tooth or median dorsal carinae on 3 rd somite, 4 th somite pleuron rounded, without marginal denticle, 5 th somite pleuron rather sharply acute posteroventrally; telson with 4 pairs of dorsolateral spinules, including a pair adjacent to lateral pair of posterior spines; stylocerite rather narrowly acute; antennal scale long as wide, distolateral tooth not reaching level of distal margin of blade; third maxilliped with epipod; pereiopods with epipods on 4 anterior pairs, 3 rd pair overreaching antennal scale by lengths of dactylus, propodus, and 1/3 of carpus, dactyl about ¼ as long as propodus, none of the pereiopods extremely slender or thread like. Parapandalus serratifrons : De Man, 1920: 146, Pl. 12, fig. 34a, c, Pl. 13, fig. 34, 34b, d, e (non Borradaile, 1900). Parapandalus spinipes : Kubo, 1965: 611, fig. 958 (non Bate, 1888). Parapandalus narval : Crosnier and Forest, 1973: 221, fig. 69a; Crosnier, 1976: 235, fig. 4b. Plesionika serratifrons : Chace, 1985: 121, figs. 55, 56; Hayashi, 1986: 139, 274, fig. 89 (non Borradaile, 1899). ...